Retro(복고) 콘텐츠 트렌드(Trend)를 통해 살펴본 사용자의 감성적 경험연구: <응답하라 1994>를 중심으로 - 신동희; 김태양; Shin, Dong-Hee; Kim, Tae-Yang (한국콘텐츠학회 논문지, 14(4), 2014)
Recently, the retro content emerges one of the highest topics in the cultural content area. This retro content has been exponentially expanded through the series of <Answer me> and the success of the <Answer me> series highlights the importance of content that can cause user's emotional experience. Along the line, this research tries to know how the retro contents draw user's emotional experience beyond the role of just user's recall for the past through the Answer me 1994 syndrome. As the result of factorial analysis for the user's emotional experience, five factories were classified: the emotional experiences by music, item, sensory, story and actors exposed in the drama. Also, the five emotional experience factories influence the relations between the viewers and retro content. Specifically, the factories for the emotional experiences are statistically significant to the viewer's satisfaction. They significantly influence the viewer's trust and attachment for the retro content as well. The influence for the emotional experience factors which affect to viewer's satisfaction are music, item, sensory, story, and actors in order. The influence on the trust about the retro content are music, sensory, story, item in order. On the other hand, the emotional experience by actors are not significantly affect to the trust for the retro content. Lastly, The influence for the attachment about the retro content are music, item, actors, sensory, and story in order. 최근 문화콘텐츠의 최고 화두는 복고이다. 하루가 다르게 발전하고 있는 스마트미디어 환경은 콘텐츠 시장에 다양성과 창의성이라는 혜택과 과제를 동시에 던져주고 있다. 최근 레트로 문화는 '응답하라' 시리즈물을 통하여 폭발적으로 확장되었으며 '응답하라'시리즈물의 성공은 사용자의 감성적 경험을 불러일으킬 수 있는 콘텐츠의 중요성을 보여주고 있다. 이러한 관점에서 본 연구는 <응답하라 1994>신드롬을 통하여 사용자의 감성적 경험을 이해하고 레트로 콘텐츠가 단순한 과거회상의 역할을 넘어 어떻게 현재에 재서사화 되어 사용자의 감성적 경험을 이끌어 내는지 고찰한다. <응답하라 1994>를 통한 시청자들의 감성적 경험에 대한 요인분석 결과 도출된 5가지 감성적 경험 요인들은 시청자와 레트로 콘텐츠 관계에 정적인 영향을 미친 것으로 분석되었으며 시청자 만족, 레트로 콘텐츠에 대한 신뢰, 레트로 콘텐츠 애착에 유의미한 영향을 미치는 것으로 나타났다. 시청자 만족에 영향을 미치는 요인별 영향력은 음악적 감성경험, 아이템 감성경험, 감각적 경험, 스토리적 감성경험의 순으로 나타났고, 레트로 콘텐츠에 대한 신뢰에 영향을 미치는 감성적 경험의 요인별 영향력은 음악적 감성경험, 감각적 경험, 스토리적 감성경험, 그리고 아이템 감성경험의 순으로 나타났으나 등장배우로 인한 감성적 경험은 유의미한 영향력을 갖지 못했다. 레트로 콘텐츠 애착에 미치는 감성적 경험의 차원별 영향력은 음악적 감성경험, 아이템 감성경험, 등장배우로 인한 감성경험, 감각적 경험, 스토리적 감성경험의 순으로 나타났다. 본 연구는 레트로가 가지고 있는 본질적인 의미를 파악하고 소비자의 감성적 경험에 기반을 둔 문화 콘텐츠의 생산 및 확산이 미디어 콘텐츠 생태계 형성 및 발전에 매우 중요한 요소임을 시사한다.